2009
DOI: 10.1016/j.bpj.2009.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Monitoring of Transferrin-Induced Endocytic Vesicle Formation by Mid-Infrared Surface Plasmon Resonance

Abstract: We report on the application of surface plasmon resonance (SPR), based on Fourier transform infrared spectroscopy in the mid-infrared wavelength range, for real-time and label-free sensing of transferrin-induced endocytic processes in human melanoma cells. The evanescent field of the mid-infrared surface plasmon penetrates deep into the cell, allowing highly sensitive SPR measurements of dynamic processes occurring at significant cellular depths. We monitored in real-time, infrared reflectivity spectra in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…The internalization and recycling of the TfR have been closely studied by multiple groups for over 2 decades. While some have observed that internalization of the TfR is linear over time regardless of Tf addition (24), others have observed an increase in the endocytic rate of this receptor in the presence of ligand (19,48,49,60). This concept of regulated internalization has been supported by studies implicating protein kinase C (PKC) (29,47) and casein kinase activation (12), increases in cytoplasmic calcium (46), and, most recently, Src activity (61).…”
Section: Discussionmentioning
confidence: 99%
“…The internalization and recycling of the TfR have been closely studied by multiple groups for over 2 decades. While some have observed that internalization of the TfR is linear over time regardless of Tf addition (24), others have observed an increase in the endocytic rate of this receptor in the presence of ligand (19,48,49,60). This concept of regulated internalization has been supported by studies implicating protein kinase C (PKC) (29,47) and casein kinase activation (12), increases in cytoplasmic calcium (46), and, most recently, Src activity (61).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is important to note that the rapid and transient (lasting up to 4 h with peptide pre-treatment) nature of the neuroprotection induced by poly-arginine peptides (Meloni et al, 2015) corresponds closely to the timeframes of endocytosis and endosomal receptor re-cycling (Gundelfinger et al, 2003;Maxfield & McGraw, 2004;Yashunsky et al, 2009). Importantly, it is known that TAT, penetratin and R9 can induce the internalisation of EGFR and TNFR in HeLa cells (Fotin-Mleczek et al, 2005).…”
Section: Proposed Neuroprotective Mechanism Of Action Used By Argininmentioning
confidence: 91%
“…So far we used this technique to study alterations in membrane cholesterol levels in HeLa cells [12], de novo formation of early endocytic transport vesicles in response to transferrin internalization by human melanoma cells [13], and detection of glucose uptake by erythrocytes [11].…”
Section: Introductionmentioning
confidence: 99%